Choosing an Assisted Living Facility - Suzanna Smith (EDIS)
“Assisted living facilities are a type of housing for frail elders and people with physical and mental disabilities who don’t need nursing care but cannot live independently. These residences offer personal care, health care, around-the-clock supervision, and other services. With a wide variety of facilities out there, selecting a residence may be difficult.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, April 2012.